The deeper, the more distinct: dissolved organic matter composition differs between soil types and diverges with depths - Charamba, Livia V. C.; Houska, Tobias; Kaiser, Klaus; Knorr, Klaus-Holger; Krause, Tobias; Chen, Huan; Krám, Pavel; Hruška, Jakub; Müller, Ingo; Kalbitz, Karsten (Frontiers in Environmental Science, 2025)
Dissolved organic matter (DOM) is a key component in the carbon and energy cycling of soil and aquatic ecosystems. Tracking DOM composition through soil profiles provides insight into the processes driving its transport and transformation. However, there is a lack of studies investigating whether DOM composition in deeper mineral soil is driven by topsoil inputs, or if processes during soil passage cause a rather uniform DOM quality irrespective of the source. Understanding the topsoil influence on subsoil DOM and depth-dependent transformation patterns is crucial for the transfer to and its fate within aquatic ecosystems. To address this knowledge gap, we examined the compositional features of DOM sampled in situ along depth profiles of four contrasting soil types (Peat, peaty Gleysol, Cambisol, Podzol) in a mountainous catchment (Ore Mountains, Germany). A combination of pyrolysis-gas chromatography/mass spectrometry and UV and fluorescence spectroscopy was used to characterize the molecular properties of DOM and similarities across the different soils and depths were achieved by Bray-Curtis dissimilarity analysis. Results revealed site-specific decreases in similarity with depth, driven by soil processes that progressively alter DOM composition. In Peat, composition remained rather similar between D1 and D2 or D3 (57-59%), likely due to constantly anoxic conditions that inhibit oxidative degradation and transformation of DOM. In the peaty Gleysol, moderate transformations were observed (41-59% similarity), likely driven by alternating redox conditions and sorptive interactions. The strongest compositional changes occurred in the Cambisol with similarity between D1 and D3 reaching 18%, suggesting microbial processing in conjunction with sorptive interactions with the mineral phase. In the Podzol, the formation of organo-metal complexes promoted selective preservation of aromatic structures. The site-specific processes led to decreases in both the number and abundance of identified shared compounds with depth, contrasting the assumption of DOM similarity across different soil types. Despite the changes with depth, subsoil DOM composition in Peat, peaty Gleysol, and Podzol still retained some imprint of topsoil sources. This study highlights how site-specific biotic and abiotic processing generates unique DOM composition that shape organic matter cycling in soils and its ecological implications in aquatic systems.